MASCC/ISOO clinical practice guidelines for the management of mucositis secondary to cancer therapy. Issue 19 (28th July 2020) - Elad, Sharon; Cheng, Karis Kin Fong; Lalla, Rajesh V.; Yarom, Noam; Hong, Catherine; Logan, Richard M.; Bowen, Joanne; Gibson, Rachel; Saunders, Deborah P.; Zadik, Yehuda; Ariyawardana, Anura; Correa, Maria Elvira; et al.
Abstract : Background: Mucositis is a significant toxicity of cancer therapy with numerous systemic sequelae. The goal of this systematic review was to update the Multinational Association of Supportive Care in Cancer and International Society of Oral Oncology (MASCC/ISOO) Clinical Practice Guidelines for the management of mucositis. Methods: The literature was reviewed systematically to identify interventions for mucositis. Studies were rated according to the presence of major and minor flaws according to previously published criteria. The body of evidence for each intervention and in each treatment setting was assigned a level of evidence based on previously published criteria. Guidelines were developed based on the level of evidence, with 3 possible guideline determinations: recommendation, suggestion, or no guideline possible . Results: The guideline covers evidence from 1197 publications related to oral or gastrointestinal mucositis. Thirteen new guidelines were developed for or against the use of various interventions in specific treatment settings, and 11 previous guidelines were confirmed after aa review of new evidence. Thirteen previously established guidelines were carried over because there was no new evidence for these interventions. Conclusions: The updated MASCC/ISOO Clinical Practice Guidelines for mucositis provide professional health caregivers with a clinical setting‐specific, evidence‐based tool to help with the management of mucositis in patients who have cancer. Abstract : The Multinational Association of Supportive Care in Cancer and the International Society of Oral Oncology developed clinical practice guidelines for the management of mucositis, with the first edition published in 2004 and periodically updated. This summary presents the 2019/2020 guidelines update, which is based on a systematic review, and generates a tool that will help clinicians to select evidence‐based interventions.